Pengaruh Variasi Parameter Filter Terhadap Harmonisa Pada Operasi PLTS Terintegrasi Sistem Tenaga Listrik - Muljono, Agung Budi; Ari Nrartha, I Made; Ginarsa, I Made; Sultan; Ketut Perdana Putra, I (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2024)
This paper provides a comprehensive harmonic picture of Photovoltaic operations integrated with the Electric Power System (Photovoltaic on-grid). Harmonics in Photovoltaic on-grid are generated from the inverter. One way to reduce harmonics is by installing a filter. Apart from reducing harmonics, filters can improve the system power factor value. This research examines the effect of variations in Photovoltaic on-grid filter parameters on inverter power capacity using Simulink/Matlab simulation. The FFT (Fast Fourier Transform) method is used to determine the harmonic order and THD of the current and voltage of the system on the side before and after the filter. The simulation results show changes in filter parameter variations for Qc (Var) values ​​giving THDi and THDv values ​​before and after filter installation using the FFT approach.